A Decomposition of Trends in Blacks' and Whites' Exposure to Other–Race Neighbors, 2001–2011. (September 2018) - Huang, Ying; South, Scott J.; Spring, Amy; Crowder, Kyle
Using data from the Panel Study of Income Dynamics and two U.S. decennial censuses, we describe trends in blacks' and whites' exposure to other–race neighbors between 2001 and 2011 and then identify the proximate sources of these trends. Our results show that whites experienced an increase in their exposure to black and other minority neighbors and a concurrent decrease in same–race neighbors. Blacks' exposure to both black and white neighbors declined somewhat between 2001 and 2011, while their exposure to nonblack minority neighbors increased substantially. Decomposition analysis reveals that increases in whites' exposure to black neighbors were driven primarily by in situ neighborhood change (i.e., by change surrounding nonmobile neighborhood residents), and only secondarily by shifting patterns of migration to neighborhoods containing more blacks and fewer whites. Changes in blacks' exposure to white neighbors were shaped by two countervailing forces. While the neighborhoods inhabited by non–mobile blacks became relatively less black and more white, residentially mobile blacks were increasingly moving to neighborhoods that were more black and less white. Increases in blacks' and whites' neighborhood ethnoracial diversity were driven almost entirely by in situ changes around nonmobile blacks and whites.